Process of Paradigm Shift in Determining Modes of Orientalist’s confrontations in Sirah writing: An Analytical Study - Ruby, Nayab; Naimat Ullah, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
The research paper grew out on the process of Paradigm shift which plays significant role in formative modes of the orientalists’ preconception and intolerance which they accomplished while inscription on purified lifetime of Muhammad (amity and greetings be upon him) but these confrontations shift its development to resolution and reconciliation by Western authors of 21st century that lead to winning factors in academic treatise of current era. The research aims to search determining modes of them, thought process of paradigm shift and its impacts. The present threads will explore modes that stimulate them to discover the Islamic inclinations over the sacred life of him. In their exposition, they have shown enthusiastic determinations to understand the observation that expands the Islamic acquaintances and articulated it in their dialectal with their patterns. The intolerance took place in academic and speculative jurisdiction of European Revival. In 21st century, number of Western authors reconciled their thoughts and interpretations for Islam. Key words: Paradigm shift, Sirah writing, Orientalist’s confrontation, winning factors of reconciliation, Academic discourse for Islam.